Distinct intestinal microbial communities of two sympatric anadromous Arctic salmonids and the effects of migration and feeding - Geraint Element; Katja Engel; Josh D. Neufeld; John M. Casselman; Peter J. Van Coeverden de Groot; Virginia K. Walker (Arctic Science, 2021)
Although intestinal microbial communities from anadromous Arctic char (Salvelinus alpinus (Linnaeus, 1758)) in Kitikmeot, Nunavut, Canada, differ depending on the timing and location of capture, determinants of gut microbiota in other wild Arctic salmonids are largely unknown. Using high-throughput 16S rRNA gene sequence data, we compared intestinal microbiota from Arctic char to those from a related and sympatric salmonid, lake whitefish (Coregonus clupeaformis (Mitchill, 1818)). Shifts in lake whitefish gut microbial community composition were observed between brackish water and freshwater, similar to impacts of salinity reported previously for Arctic char. Despite these similarities, gut community profiles for the two salmonids differed, with whitefish having higher diversities and increased proportions of taxa affiliated with potential pathogens. Geography seemed to have a greater impact on freshwater whitefish gut microbiota than on corresponding Arctic char. Additionally, microbiota diversity was significantly more affected by feeding behavior in whitefish compared with sympatric Arctic char. As sampled whitefish were at their northern range limits and grew slowly, we speculate that they, and their microbial consortia, could be more vulnerable to certain abiotic and biotic factors than Arctic char, which are well adapted to conditions found in these high latitude environments and have the most northern distribution of any freshwater fish.